We are branches - Sidman, Joyce (Clarion Books, an imprint of HarperCollins Publishers, 2023)
Branches are all around us: in butterfly wings, on gecko toes, in flowers, frost, and mud. Whether as electricity moving across the sky or rivers flowing to the sea, branches are nature's most efficient way to spread and to connect. They are even found inside our own bodies, helping us reach and grow with each breath and heartbeat. Branches--strong, hopeful, beautiful--are the shape of life. How many can you find?